(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The study evaluated solid waste transformation to wealth in Owerri Municipal and its effect to the environment. The descriptive surveying method was used while making use of a questionnaire. It was administered to hundred (100) respondents among scavengers, individuals, men / women in solid waste and officials of ISWAMA (Imo State Waste Agent Management Agency). The result showed that carton with mean of 3.61 is the solid waste that highly affected the serenity of the city while wood with mean of 2.60 had least effect. The most harmful effect was noticed in accident with mean of 3.59 while the least effect is in nuisance with mean of 3.17. ISWAMA officials with mean of 3.63 disposed solid waste effectively while street waste sites with mean of 3.25 had the least effect. Wood with mean of 3.63 is the most solid waste that is being transformed to wealth while rubber with mean of 2.67 is the least. Carton with the mean of 3.72 gives the highest profit to people in its business while rubber with mean of 3.54 yielded the least profit. Mechanical transformation of wood with 2.46 mean is the highest among solid wastes while plastic with the mean of 1.71 is the least solid waste that is being recycled mechanically. Solid waste was discovered to have affected the serenity of Owerri municipal, requires active management; it is a source of wealth, not recycled mechanically. The study provides data to guide policy on waste-to-wealth.